Validity and Reliability of the Persian Version of Cyber Pornography Use Inventory-9 Among Iranian Students - Mehdi Darvish Molla; Zahra Nikmanesh (Gonabad University of Medical Sciences, 2020)
Background: This study aimed to examine the validity and reliability of the Persian version of cyber pornography use inventory-9 (CPUI-9) in the Iranian context.  Methods: The current research is a descriptive cross-sectional study. The study sample included 262 (190 male and 72 female) university students, who were selected by multi-stage cluster sampling method. The psychometric properties of the Persian version of CPUI-9 were assessed in this study.  Results: The descriptive findings indicated that the Mean±SD age of the participants was 21.64 (2.36) years. Psychometric analyses indicated the high validity and reliability of this inventory. The exploratory factor analysis identified three factors that are consistent with the results of previous studies. Besides, confirmatory factor analysis revealed the model goodness of fit. The Cronbach alpha coefficient of CPUI-9 was also found as 0.87. Additionally, the concurrent validity showed that CPUI-9 was significantly and positively related to depression, anxiety, and stress (P<0.01).  Conclusion: Finally, the study results supported the reliability and validity of the Persian version of CPUI-9 among Guilan university students. Moreover, the findings were in line with the results of the original study.